Multiplex analysis platform for evaluation of endocrine disruption of emerging contaminants against human steroid hormone receptors using autobioluminescent yeast bioassay: Application to bisphenols - Yuan Huang; Wei Zhang; Ruiguo Wang; Zhiming Xiao; John P. Giesy; Liming Wu; Xiaoou Su (Emerging Contaminants)
Emerging synthetic or derivative chemicals have drawn global concern due to their potential endocrine-disrupting effects, either as agonists or antagonists or through indirect effects on enzymes of signal transduction pathways. Currently, in vitro screening models are limited to poor tolerance, robustness, high cost and need for sphisticated equipment or complex procedures that require high levels of expertise. Herein, a multiplex analysis platform based on autobioluminescent yeast strains, including BLYhERαS, BLYhERβS, BLYhPRS, BLYhARS, BLYhMRS, and BLYhGRS, was developed for use in easy, rapid, robust, and sensitive screening for potential modulation of endocrine systems. Methods were applied to assess endocrine-disrupting effects of Bisphenol A (BPA) and its alternatives. Disrupting activities of bisphenols (BPs) varied greatly, and some BPA substitutes exerted more potent activities than those of BPA. Most BPs were primarily agonists of ERα and ERβ, while others were antagonists to AR, PR, GR, and MR. BPP and BPM exhibited non-monotonic dose-response relationships toward ERα and ERβ, and BHPF and BPG displayed converse disrupting activities to ERα and ERβ. Overall, the bioassay system provides an efficient tool for comprehensive evaluation of endocrine-disrupting activities of emerging contaminants.